(untitled) (Journal of Applied Learning and Teaching, 2025)
The use of Generative Artificial Intelligence (GAI) in higher education has garnered significant attention from scholars and researchers since the release of ChatGPT, one of the prominent GAI tools, in late 2022. While academic communities are increasingly recognizing the potential of GAI in teaching and learning, concerns persist regarding the impact of individual backgrounds and employment statuses on attitudes toward GAI, particularly in private higher education. This paper examines the perspectives of academic staff across different disciplines and employment statuses on their familiarity with and incorporation of GAI technologies in teaching. It emphasizes how to integrate GAI technologies effectively into teaching while upholding academic integrity and ensuring the quality of education. The findings, derived from an online survey and descriptive analysis, reveal significant variation in GAI familiarity among disciplines, as well as differing approaches to integrating GAI tools into teaching practices and formulating policies to maintain academic integrity. Notably, full-time staff are generally more familiar with GAI than their casual counterparts. While most teaching staff are open to students using GAI in their studies, concerns about potential breaches of academic integrity, particularly in assessments, remain prominent. To address these concerns, we recommend developing a transparent academic integrity policy along with clear guidelines for GAI use tailored to different disciplines and employment statuses. Such measures would foster an innovative and creative learning environment while safeguarding the quality of education.